Fluoxetine increases astrocytic glucose uptake and glycolysis in corticosterone-induced depression through restricting GR-TXNIP-GLUT1 Pathway - Pan, Shu-Man; Zhou, Yi-Fan; Zuo, Na; Jiao, Rui-Qing; Kong, Ling-Dong; Pan, Ying (Frontiers in Pharmacology, 2022)
Antidepressant fluoxetine can affect cerebral glucose metabolism in clinic, but the underlying molecular mechanism remains poorly understood. Here, we examined the effect of fluoxetine on brain regional glucose metabolism in depression, and explored the molecular mechanism. Fluoxetine was found to recover the decrease of 18F-FDG signal in prefrontal cortex (PFC), and increased 2-NBDG uptake in an astrocyte-specific manner in ex vivo cultured PFC slices from corticosterone-induced depression model of rats, which were consistent with its improvement of animal depressive behaviors. Furthermore, fluoxetine restricted nuclear translocation of glucocorticoid receptor (GR) to suppress the transcription of thioredoxin interacting protein (TXNIP). Subsequently, it promoted glucose transporter 1 (GLUT1)-mediated glucose uptake and glycolysis in PFC astrocytes through suppressing TXNIP expression under corticosterone-induced depressive state. More importantly, fluoxetine could improve astrocytic glucose metabolism in corticosterone-stimulated of cultured primary astrocytes via TXNIP-GLUT1 pathway. This study demonstrated that fluoxetine increased astrocytic glucose uptake and glycolysis under depressive state via restricting GR-TXNIP-GLUT1 pathway. These findings suggested the modulation of astrocytic glucose metabolism by fluoxetine as a novel antidepressant mechanism of its action.